Role of MSME in rural development - KUMAR, DR. P. PRAVEEN; MS. N. RAJALAKSHMI, (The journal of contemporary issues in business and government, 2020)
Microfinance moneylenders give little credits to current and hopeful entrepreneurs. These advances help give individuals who might not have the credit or the admittance to conventional financing the chance to procure a higher pay and give occupations to their nearby networks. The measure of microfinance advances differ by loan specialist and can go from $25 up to $2,000. Descriptive research design is adopted to measure the selected topics. The sample size of the study is 46 members of MSME. The study primarily uses primary data. The tools of frequency analysis, mean analysis and ANOVA used in the study to analyse the data.